Factors Associated with Edentulism among Adult Users of Public Oral Health Services in Victoria, Australia - Rodrigo Mariño; Hanny Calache; Martin Whelan (Dentistry Journal, 2014)
This study examined edentulism (total absence of natural dentition) trends among adults’ users of public oral health care in Victoria, Australia and factors associated with these trends. The sample comprised 13,578 dental clients of public oral health care services, collected between July 2008 and June 2009, from which data were complete. The group of edentulous clients represented 6.8% of all clients. Older participants were more likely to be edentulous (OR = 3.95; 95% CI 3.53–4.43). By language spoken at home, those who spoke English were more likely to be edentulous than those who spoke other languages (OR = 1.29; 95% CI 1.02–1.63). Aboriginal clients were more likely to be edentulous than non-Aboriginal clients (OR = 2.21; 95% CI 1.15–4.27). By region of residence, clients living in rural locations were more likely to be edentulous than those living in urban regions (OR = 1.53; 95% CI 1.32–1.78). The full model explained 16.8% of the variance in being edentulous. Findings in edentulism were lower than what was reported by the National Survey of Adult Oral Health. However, despite this trend, significant variations existed across urban and rural locations. Innovative public health programs and services are essential to prevent inequalities in oral health diseases and conditions for rural populations.